(3TQM GdhGajIs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s ((3fYeI Hf YdGA GdOjf GdWQjMjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3bhdg(B: (3GddaX Ef GSJYed ajeG hVY dg aMbjbI(B. (3aLd GdebSe eWdb GddaX(B...s
(3BNQgG (B:s
(3CbSGe GdeLGR dcfg NdGa GdJMbjb heeG jOd Ydi aSGOg CfG fYde HGdVQhQI eHGdZI aj OYhi GdTLGYI ceG aj GdaQb HjfgeG(B. (3bO hbY GdaQGZ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B113s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs